Improved Power Plant Performance Utilizing Hybrid Performance Test Execution (HYPER-X) - Satyadi, Hakim; Kurniawan, Agus; Fadholi, Fadholi (Department of Mechanical and Industrial Engineering, 2024)
Alongside the PLN Transformation Program, digitization has emerged as a crucial foundation that the company continues to develop amidst the disruptions caused by modern technology. This effort aims to establish lean and cost-efficient processes. Therefore, companies ensure sustainability and maintain competitiveness amidst increasingly fierce future competition. To establish lean and cost-efficient processes Currently, performance tests are carried out conventionally by collecting data through trending DCS (Distributed Control System) and processing data using Excel, which is carried out once a month for each unit. From this, the performance test results for each unit are only obtained once a month so that the performance of new units can be seen over a long period. Therefore, a longer period is required to observe the performance of new units. To solve the problem above, a performance test unit process was made with a newer concept, namely by adding digitization in it, namely hybrid performance test execution, abbreviated as Hyper-X, the hope is that from the start data collection and processing can be done quickly so that unit performance conditions can be obtained more quickly. Fast and can be monitored in real time. The results obtained from Hyper-X are in the form of energy power indicators, heat rate losses, and costs as well as analysis and recommendations that can provide operating guidelines so that the unit operates more optimally and efficiently. Hyper-X can reduce the potential loss heat rate by 35 kcal/kwh or equivalence with IDR 141,560,000.00. As for other benefits obtained, it facilitates the identification of areas experiencing heat rate losses determines the follow-up execution steps for repairs and fosters a professional and learner culture to solve problems.